2012
DOI: 10.1371/journal.pone.0043639
|View full text |Cite
|
Sign up to set email alerts
|

Low Socioeconomic Status Is Associated with Prolonged Times to Assessment and Treatment, Sepsis and Infectious Death in Pediatric Fever in El Salvador

Abstract: BackgroundInfection remains the most common cause of death from toxicity in children with cancer in low- and middle-income countries. Rapid administration of antibiotics when fever develops can prevent progression to sepsis and shock, and serves as an important indicator of the quality of care in children with acute lymphoblastic leukemia and acute myeloid leukemia. We analyzed factors associated with (1) Longer times from fever onset to hospital presentation/antibiotic treatment and (2) Sepsis and infection-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 22 publications
2
46
3
2
Order By: Relevance
“…This is not surprising considering how rapidly Burkitt lymphoma can grow, such that any treatment gaps provide an opening for disease to progress (Patte et al , ). The intense block regimens in HIC include high‐dose methotrexate, alkylating agents, anthracyclines, vincristine, glucocorticoids and intrathecal methotrexate in doses that induce severe neutropenia, lymphopenia, thrombocytopenia and mucositis, requiring intense supportive care including management of infection, haemorrhage, drug‐specific toxicities and nutrition (Patte et al , ; Howard et al , , ; Gavidia et al , ; Israels et al , ; Bhojwani et al , ; Gupta et al , ; Ladas et al , ). Patients usually develop profound aplasia and opportunistic infections, which necessitate rapid access to intensive life‐support.…”
Section: Protocol‐based Carementioning
confidence: 99%
“…This is not surprising considering how rapidly Burkitt lymphoma can grow, such that any treatment gaps provide an opening for disease to progress (Patte et al , ). The intense block regimens in HIC include high‐dose methotrexate, alkylating agents, anthracyclines, vincristine, glucocorticoids and intrathecal methotrexate in doses that induce severe neutropenia, lymphopenia, thrombocytopenia and mucositis, requiring intense supportive care including management of infection, haemorrhage, drug‐specific toxicities and nutrition (Patte et al , ; Howard et al , , ; Gavidia et al , ; Israels et al , ; Bhojwani et al , ; Gupta et al , ; Ladas et al , ). Patients usually develop profound aplasia and opportunistic infections, which necessitate rapid access to intensive life‐support.…”
Section: Protocol‐based Carementioning
confidence: 99%
“…A high incidence of sepsis has been demonstrated in pediatric patients receiving chemotherapy, approximately 12.8% in children aged 1-9 years and 17.4% in children aged 10 Barriers to Cure of Childhood Cancer  neutropenia a serious and worrying complication in pediatric cancer treatment [17]. Studies on febrile neutropenia from PODC are few [18], but febrile neutropenia remains a major cause of hospitalization apart from admissions for chemotherapy administration. A study from India on patterns of mortality in children with ALL identified sepsis (53.3%) and bleeding (15.7%) as the most common causes of mortality [19].…”
Section: Sepsis and Treatment-related Toxicitymentioning
confidence: 99%
“…This results in longer hospital stay and increased cost of treatment. [6] The etiological pattern in both Indian and Western studies over the years are more or less similar showing infections as the most common cause. TB was found to be the most common infection causing FUO not only in India but also in studies done in Turkey and Taiwan.…”
Section: Discussionmentioning
confidence: 99%